2018
DOI: 10.1155/2018/8594767
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid Functions as a Novel Agonist of PPARγ2 during the Differentiation of Mouse 3T3-L1 Preadipocytes

Abstract: Rosiglitazone (RG) is a well-known activator of peroxisome proliferator-activated receptor-gamma (PPARγ) and used to treat hyperglycemia and type 2 diabetes; however, its clinical application has been confounded by adverse side effects. Here, we assessed the roles of chlorogenic acid (CGA), a phenolic secondary metabolite found in many fruits and vegetables, on the differentiation and lipolysis of mouse 3T3-L1 preadipocytes. The results showed that CGA promoted differentiation in vitro according to oil red O s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…It is known that CD36/SR-B2 expression is regulated by agonists of the nuclear peroxisome proliferator-activated receptors (PPAR). Recent studies performed on 3T3L1 preadipocytes identified chlorogenic acid as PPARγ2 (20 µM) and PPARα (50 µM) agonist [46,47]. Our results revealed that V. opulus did not influence the expression of the gene encoding PPARα allowing us to suspect that other V. opulus polyphenolic compounds may act as PPAR or CD36/SR-B2 antagonist.…”
Section: Resultsmentioning
confidence: 46%
“…It is known that CD36/SR-B2 expression is regulated by agonists of the nuclear peroxisome proliferator-activated receptors (PPAR). Recent studies performed on 3T3L1 preadipocytes identified chlorogenic acid as PPARγ2 (20 µM) and PPARα (50 µM) agonist [46,47]. Our results revealed that V. opulus did not influence the expression of the gene encoding PPARα allowing us to suspect that other V. opulus polyphenolic compounds may act as PPAR or CD36/SR-B2 antagonist.…”
Section: Resultsmentioning
confidence: 46%
“…They were able to down-regulate the expression of adipogenic transcription factors (PPARγ and C/EBP) and adipocyte-specific proteins (leptin), as well as up-regulate adiponectin. In comparison, other study performed with 3T3-L1 differentiated cells identified chlorogenic acid as an agonist of PPARγ2, which promoted adipocyte differentiation via the elevation of PPARγ2, CEBP and SREBP-1 mRNA and protein level [ 54 ]. Nevertheless, the other phenolic compounds identified in V. opulus fruit were proved to decrease the adipogenesis process [ 55 , 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, PPARγ transcriptional potential could be modulated on different levels: by the regulation of mRNA and protein levels, as well as conformational changes made after its binding with ligands leading to protein subcellular distribution, heterodimers’ formation, and, finally, binding with peroxisome proliferator hormone response elements present in promoters of PPAR-responsive genes. The studies performed recently identified chlorogenic acid as an agonist of the PPARγ2 receptor responsible for the enhanced differentiation of 3T3-L1 cells [ 54 ]. In the identified molecular mechanism downregulation of adipocyte differentiation-inhibitor gene, Pref1 was observed, which was accompanied by the upregulation of CEBP and SREBP-1 transcriptional factors.…”
Section: Resultsmentioning
confidence: 99%
“…Vanillic acid presented a strong effect reducing TAG content in 3T3-L1 adipocytes through the reduction of AdipoQ , Plin1 , and Fabp4 expression [64]. Chlorogenic acid has shown to increase lipolysis and up-regulate the expression of lipases ( Hsl and Dgat1 ) [65,66]. Similarly, caffeine has exhibited potential to up-regulate HSL and AGTL and increase lipolysis, reducing TAG content in 3T3-L1 cells [67,68].…”
Section: Resultsmentioning
confidence: 99%